Avaliação dos efeitos da introdução de videocasts assíncronos na motivação e na aprendizagem de estudantes do internato médico - Vieira, Fabio Pizzamiglio (2022)
Introduction: Educational systems are undergoing significant changes, especially with refer to the admission of Technologies of Information and Communication (TsIC) as pedagogical resources. In times of social isolation, distance learning has been increasingly present in higher education institutions that previously adopted traditional models in the teaching-learning environment. In this context, evaluating motivation and learning can contribute to the analysis and decision of a more efficient educational proposal. Objective: To evaluate the learning and motivation of medical students in the ophthalmology discipline of the medical internship through the comparison between traditional classes and videocasts. Methodology: This is na experimental research applied to 35 students of the (7th) seventh period of the medical course at UNIFENAS, in Alfenas (MG), in 2021. In the experiments, traditional theoretical classes were given (Traditional Group – TG) and a class containing videocasts (Videocast Group – VG) about the topic of diabetic retinopathy. A sociodemographic questionnaire was applied, as well as a pre-test (PrT) before the traditional class, and later the groups answered the Post Test 1 (PsT1) about this class model. Afterwards, the students were randomly divided into the TG and GV groups, and after 7 days, a second questionnaire Post Test 2 (PsT2) was applied to these groups. Through the IMMS-BRV questionnaire, interventions were evaluated accord to student motivation, as well as knowledge retention (immediate and late post-test). Results: According to the study group no significant differences (p ≥ 0.05) were observed in relation to the scores obtained in the pre-test (PrT) and in the post-intervention (PsT2). However, in the grades obtained after the theoretical class (PsT1) significantly higher values were identified in the GV group when compared to the TG group. As for motivation, in both groups of students, TG and VG, it was found to be high, with no difference between the groups. Conclusion: The use of asynchronous videocasts in the ophthalmology discipline resulted in proficiency similar to that obtained by using traditional study materials. There was high motivation in the group of students who used the videocasts as well as in the group that was exposed to traditional teaching materials. Thus, both forms of study will be able to be used, respecting the learning profile of each student.